MODEL SANTAI: INOVASI PEMBELAJARAN MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS, KERJASAMA, KECERDASAN MUSIKAL DAN INTERPERSONAL SISWA SEKOLAH DASAR: PENELITIAN TINDAKAN KELAS - Muhammad Adiattoni; Akhmad Riandy Agusta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low activity of teachers and students, critical thinking skills, cooperation, and musical and interpersonal intelligence in science learning. This is caused by a monotonous learning model, lack of variety, and minimal student involvement. The solution offered is the implementation of the SANTAI learning model. The model is a combination of learning models Problem Basic Learning, Group Investigation, dan Talking Stick. This study aims to describe the activities of teachers and students and analyze the improvement of skills and student learning outcomes. This Classroom Action Research (CAR) was conducted during three meetings in the second semester of the 2024/2025 academic year in class IV of SDN Kamayahan, with 8 students as subjects. Data were collected through observation and written tests, then analyzed descriptively qualitatively and quantitatively. The results of the study showed a significant increase in various aspects, such as teacher activity (very good), student activity (43% to 88%), critical thinking (43% to 88%), cooperation (57% to 100%), musical intelligence (29% to 88%), interpersonal intelligence (71% to 100%), and learning outcomes (43% to 100%). In conclusion, the SANTAI learning model is effective in improving various aspects of learning and is recommended as an alternative innovative model for teachers, principals, and researchers.